Influenza vaccination coverage rates and other related factors in high-risk groups in Birjand, East of Iran. (November 2022) - Ebrahimzadeh, Azadeh; Bijari, Bita; Azarnoosh, Amin; Shakhs Emampour, Fatemeh
Background and Aims: Influenza is an acute respiratory disease with the highest mortality rate in the high-risk groups. Vaccination is a key public health strategy to prevent influenza in high-risk people. This study aimed to assess the influenza vaccination coverage rate and identify its demographic determinants in patients with end-stage renal disease (ESRD), chronic obstructive pulmonary disease (COPD), and diabetes in Birjand, Eastern Iran. Methods: This cross-sectional study included 400 patients (300 diabetic, 60 dialysis, and 40 COPD patients) from September 2017 to August 2018. Using interview method, we completed a questionnaire containing the patients' demographic characteristics, questions about patients' knowledge and attitude toward influenza vaccination, the influenza vaccination history, and the most common causes for vaccination. The relationship between the type of disease and patients' characteristics (exposure) with vaccination coverage (outcome) was investigated. Results: The mean age of participants was 58.7 ± 11.3 years. Also, 58.8% of the patients received at least one dose of the vaccine and the regular injection rate was 32.8%. The coverage of influenza vaccine in dialysis patients was significantly higher than other patients ( p < 0.001). The mean knowledge score was 6.17 ± 2.15 out of maximum 9 scores. There was a positive association between age [ p = 0.001, odds ratio (OR) = 1.04] and patients' knowledge ( p < 0.001, OR = 1.42) with the vaccination coverage. Conclusion: The coverage of influenza vaccine in high-risk patients in Birjand was low. Hence, it is essential to increase the knowledge of high-risk groups about the importance of influenza vaccination and facilitate their access to vaccines.